Method for manufacturing electrode, electrode, and battery
By fixing the conductive material with an adhesive to the surface of the active material particles in the electrode manufacturing and mixing it with the fibrated PTFE, the problem of insufficient electron conductivity of the existing electrode is solved, and efficient electron conductivity and environmentally friendly manufacturing is achieved cost.
Patent Information
- Application Number
- CN202410536188.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-09
- Filing Date
- 2024-04-30
- Publication Date
- 2025-02-18
AI Technical Summary
There is still room for improvement in the electron conductivity of the existing electrodes, especially without the use of solvents.
By mixing active material particles, conductive material and adhesive, the conductive material is fixed on the surface of the active material particles, and mixing it with polytetrafluoroethylene (PTFE) on this basis, PTFE is fibrated to form an electrode layer.
An electrode with excellent electron conductivity is achieved, ensuring the sufficient contact area between the active material particles and the conductive material, improving the overall performance of the electrode, and reducing manufacturing costs and environmental impact without using solvents.
Smart Images

Figure BDA0004819652350000091
Abstract
Description
Technical Field
[0001] The present disclosure relates to a method for manufacturing an electrode, an electrode, and a battery. Background Art
[0002] In batteries such as lithium-ion secondary batteries, electrodes are used in which active material particles are fixed with a binder on the surface of a current collector such as a metal foil. As methods for manufacturing electrodes, there are known methods of coating the surface of a current collector with a composition prepared by mixing active material particles and a binder with a solvent (also known as a wet method), and methods of fixing active material particles to a current collector with a binder without using a solvent (also known as a dry method).
[0003] As a method for manufacturing an electrode using a dry process, a method of using a resin having a property of being fibrillated (fibrillated) when a shear force is applied as a binder is proposed. For example, Japanese Patent Publication No. 2022-3694 describes the following method: PTFE in a mixture containing active material particles and polytetrafluoroethylene (PTFE) is fibrillated to make an electrode film, and then the electrode film is integrated with a collector to manufacture an electrode. Summary of the invention
[0004] The electrode obtained by the method described in Japanese Patent Application Laid-Open No. 2022-3694 still has room for improvement in terms of electron conductivity. One embodiment of the present disclosure aims to provide a method for producing an electrode with excellent electron conductivity, an electrode with excellent electron conductivity, and a battery including an electrode with excellent electron conductivity.
[0005] Means for solving the above-mentioned problems include the following embodiments.
[0006] <1> A method for manufacturing an electrode, comprising: a step of kneading active material particles, a conductive material, and a binder to fix the conductive material to at least a portion of the surface of the active material particles; a step of mixing the active material particles to which the conductive material is fixed by the binder with polytetrafluoroethylene to obtain a mixture; and a step of fibrillating the polytetrafluoroethylene in the mixture.
[0007] <2> The method for producing an electrode according to <1>, wherein the coverage of the active material particles with the conductive material is 10% or more.
[0008] <3> An electrode comprising a current collector and an electrode layer, wherein the electrode layer comprises active material particles having a conductive material fixed to at least a portion of a surface thereof with a binder, and fibrous polytetrafluoroethylene.
[0009] <4> The electrode according to <3>, wherein the coverage of the active material particles by the conductive material is 10% or more.
[0010] <5> A battery comprising the electrode according to <3> or <4>.
[0011] According to one embodiment of the present disclosure, a method for producing an electrode having excellent electron conductivity, an electrode having excellent electron conductivity, and a battery including the electrode having excellent electron conductivity are provided. DETAILED DESCRIPTION
[0012] In the present disclosure, the numerical range represented by "to" refers to the range in which the numerical values recorded before and after "to" are respectively included as the minimum and maximum values. In the numerical range recorded in stages in the present disclosure, the upper limit or lower limit recorded in a certain numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In the numerical range recorded in the present disclosure, the upper limit or lower limit recorded in a certain numerical range can be replaced by the value shown in the embodiment. In the present disclosure, the term "process" is not only an independent process, but also is included in this term as long as the purpose expected by the process can be achieved even if it cannot be clearly distinguished from other processes. In the present disclosure, the combination of more than two preferred schemes is a more preferred scheme. In the present disclosure, the amount of each component, when there are multiple substances equivalent to each component, refers to the total amount of multiple substances unless otherwise specified.
[0013] Electrode manufacturing method
[0014] The manufacturing method of the electrode disclosed in the present invention includes: a process of kneading active material particles, a conductive material and a binder to fix the conductive material to at least a portion of the surface of the active material particles; a process of mixing the active material particles to which the conductive material is fixed by the binder with PTFE to obtain a mixture; and a process of fiberizing the PTFE in the mixture.
[0015] The electrode manufactured by the method disclosed in the present invention shows excellent electronic conductivity compared with the electrode formed by the mixture obtained by mixing active material particles, conductive material and PTFE at the same time. The reason is, for example, considered to be as follows. If the PTFE is fibrillated without fixing the conductive material to the active material particles with an adhesive, the conductive material enters the fibrous PTFE, and the contact area between the active material particles and the conductive material cannot be fully ensured. In contrast, in the method disclosed in the present invention, before the PTFE is fibrillated, the conductive material is fixed to the surface of the active material particles with an adhesive. Therefore, after the PTFE is fibrillated, the conductive material is not easy to be collected into the fibrous PTFE, and the contact area between the active material particles and the conductive material is fully ensured. As a result, good electronic conductivity is achieved. Furthermore, in the method disclosed in the present invention, the conductive material is fixed to the active material particles using an adhesive (adhesive). Therefore, compared with the situation where the conductive material is fixed to the active material particles without using an adhesive, the conductive material is difficult to separate from the active material particles, and the contact area between the conductive material and the active material particles is easily ensured.
[0016] According to the method disclosed in the present invention, an electrode can be manufactured without using a solvent. Therefore, the method disclosed in the present invention is advantageous in reducing the manufacturing cost of the electrode and reducing the impact on the environment and organisms.
[0017] Hereinafter, the process of mixing active material particles, a conductive material, and a binder to fix the conductive material on at least a portion of the surface of the active material particles is also referred to as "process 1", the process of mixing the active material particles fixed with the conductive material and PTFE to obtain a mixture is also referred to as "process 2", and the process of fiberizing the PTFE in the mixture is also referred to as "process 3".
[0018] Process 1
[0019] In step 1, active material particles, a conductive material, and a binder are kneaded, and the conductive material is fixed to at least a portion of the surface of the active material particles. There is no particular limitation on the type of active material particles used in this step, and they can be selected from materials generally used in electrode manufacturing. The active material particles can be positive electrode active material particles or negative electrode active material particles.
[0020] As the positive electrode active material, lithium transition metal composite oxides can be listed. As transition metals, Ni, Co, Mn, Al, B, Mg, Ti, V, Cr, Fe, Cu, Zn, Ga, Sr, Zr, Nb, In, Sn, Ta, W, etc. can be listed. Among them, preferably a lithium transition metal composite oxide containing at least one selected from Ni, Co and Mn, more preferably a lithium transition metal composite oxide (NCM, nickel cobalt manganese oxide) containing Ni, Co and Mn. As lithium transition metal composite oxides, specifically, lithium cobaltate (LiCoO2), lithium nickelate (LiNiO2), lithium manganate (LiMnO2), their composite oxides (LiCo x Ni y Mn z O2, x+y+z=1), a composite oxide containing an additional element M' (LiCo a Ni b Mn c M' d O2, a+b+c+d=1, M': Al, Mg, Ti, Zr or Ge), spinel lithium manganese oxide (LiMn2O4), olivine LiMPO4 (M: Co, Ni, Mn, Fe), etc. The positive electrode active material used in the manufacture of the electrode can be a single type or two or more types. There is no particular restriction on the volume average particle size of the positive electrode active material particles, for example, it can be selected from the range of 5μm to 30μm.
[0021] As the negative electrode active material, specifically, carbon materials such as graphite, soft carbon, and hard carbon; silicon, etc. can be listed. The negative electrode active material used in the manufacture of the electrode can be a single type or two or more types. There is no particular restriction on the volume average particle size of the negative electrode active material particles, for example, it can be selected from the range of 5 μm to 30 μm.
[0022] In the present disclosure, the volume average particle size of particles is a value (D50) at which the accumulation from the smaller diameter side in a volume-based particle size distribution measured by a laser diffraction / scattering method becomes 50%.
[0023] There is no particular limitation on the type of conductive material used in this step, and it can be selected from materials generally used in the manufacture of electrodes. As conductive materials, specifically, carbon materials such as carbon black (acetylene black, thermal black, furnace black, etc.), carbon nanotubes, and graphite can be cited. The conductive material used in the manufacture of the electrode may be a single type or two or more types.
[0024] There is no particular restriction on the type of adhesive used in this process, and it is possible to select from the materials generally used in the manufacture of the battery. As adhesive, specifically, polyvinylidene fluoride, polyethylene, polypropylene, polyethylene terephthalate, cellulose, nitrocellulose, carboxymethyl cellulose, polyethylene oxide, polyepichlorohydrin, polyacrylonitrile, styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber (NBR), polyacrylate, polymethacrylate, etc. can be listed. The adhesive used in this process can be used alone as one, or more than two. From the viewpoints of bonding strength, affinity with PTFE, electrolyte resistance, etc., as adhesive, polyvinylidene fluoride (PVdF) is preferred.
[0025] From the viewpoint of obtaining a sufficient improvement effect on electron conductivity, the surface coverage of the active material particles by the conductive material is preferably 10% or more, more preferably 20% or more, and further preferably 30% or more. The surface coverage of the active material particles by the conductive material may be 80% or less, 70% or less, 60% or less, or 50% or less.
[0026] The surface coverage of the active material particles generated by the conductive material is measured by image analysis. As an image analysis method, a method of C mapping using energy dispersive X-ray spectroscopy (EDX) can be cited. Specifically, a scanning electron microscope (SEM) is used to observe the active material particles fixed with the conductive material using an adhesive, and C mapping is implemented using EDX. The region X corresponding to the active material particles and the region Y where the conductive material (C) exists in the region X are binarized, and the coverage is calculated according to the following formula.
[0027] Coverage (%) = (area of Y / area of X) × 100
[0028] In this process, the method of mixing the active material particles, the conductive material and the binder is not particularly limited as long as the conductive material can be fixed to the surface of the active material particles, and can be implemented using known means. Relative to 100 parts by mass of the active material particles, the amount of the conductive material can be selected, for example, from 0.1 parts by mass to 10 parts by mass, or 1 part by mass to 5 parts by mass. Relative to 100 parts by mass of the active material particles, the amount of the binder can be selected, for example, from 0.1 parts by mass to 10 parts by mass, or 1 part by mass to 5 parts by mass.
[0029] Process 2
[0030] In step 2, active material particles fixed with a conductive material (active material particles fixed with a conductive material using an adhesive) are mixed with PTFE to obtain a mixture. There is no particular restriction on the mixing method, and it can be implemented using known means. The amount of PTFE can be selected from the range of 0.1 to 10 parts by mass, or 1 to 5 parts by mass, relative to 100 parts by mass of active material particles in the mixture.
[0031] The PTFE mixed with the active material in step 2 may be in the form of particles. The mixture obtained in step 2 may not contain a solvent. In step 2, at least a portion of the PTFE may be fibrillated, and a granulated body in which the active material particles are bound by the fibrillated PTFE may be produced.
[0032] The mixture of active material particles and PTFE to which a conductive material is fixed by an adhesive may include an adhesive other than PTFE. The adhesive other than PTFE may be selected from the above-mentioned adhesives, for example. When the mixture includes an adhesive other than PTFE, its content may be less than 20 parts by mass, less than 10 parts by mass, or less than 5% by mass relative to 100 parts by mass of PTFE.
[0033] Process 3
[0034] In operation 3, the PTFE in the mixture obtained in operation 2 is Fibrated. There is no particular restriction on the method of PTFE Fibration, and known means can be used to implement. From the viewpoint of workability when the mixture after PEFE Fibration is integrated with the collector, in operation 3, preferably PTFE Fibration is formed into a sheet when the mixture is shaped into a sheet. As the method of PTFE Fibration is formed into a sheet when the mixture is shaped into a sheet, for example, the calendering process using a roller press can be listed.
[0035] The thickness of the molded body obtained by molding the mixture into a sheet is not particularly limited and can be adjusted according to the desired thickness of the electrode layer. For example, the thickness of the molded body can be selected from the range of 10 μm to 200 μm.
[0036] In operation 3, the mixture after PTFE Fibration, the preferred sheet-like molded body and the collector are integrated to form an electrode. The method of integrating the mixture after PTFE Fibration and the collector is not particularly limited, and known means can be used to implement. For example, a roller press, a plate press, etc. can be used to press the mixture and the collector. The material of the collector is not particularly limited, and can be selected from known materials such as aluminum, copper, nickel, titanium, stainless steel, etc.
[0037] electrode
[0038] The electrode disclosed in the present invention includes a current collector and an electrode layer, wherein the electrode layer includes active material particles of a conductive material and fibrous PTFE (PTFE fiber) fixed to at least a portion of the surface thereof by a binder.
[0039] The electrode disclosed in the present invention exhibits excellent electron conductivity compared to an electrode in which a conductive material is not fixed to the surface of active material particles by a binder.
[0040] The detailed information and preferred embodiments of the electrode and each material contained in the electrode disclosed in the present invention are the same as the detailed information and preferred embodiments of the electrode produced by the above-mentioned method for producing an electrode and each material used.
[0041] The electrode of the present disclosure may further include a current collector and a member other than the electrode layer including active material particles and PTFE fibers. For example, the electrode of the present disclosure may further include an electrode layer that does not contain PTFE fibers.
[0042] Battery
[0043] The battery of the present disclosure includes the electrode of the present disclosure described above. The battery of the present disclosure includes the electrode of the present disclosure as at least one of a positive electrode and a negative electrode, and in one embodiment, includes the electrode of the present disclosure as a positive electrode.
[0044] There is no particular limitation on the type of battery disclosed herein, and the battery can be selected from lithium-ion secondary batteries (including liquid batteries and all-solid batteries), lead batteries, nickel-hydrogen batteries, nickel-cadmium batteries, nickel-iron batteries, nickel-zinc batteries, silver oxide-zinc batteries, cobalt-titanium-lithium secondary batteries, sodium-ion secondary batteries and the like.
[0045] The present disclosure will be described in more detail below using examples, but the present invention is not limited to these examples.
[0046] Example
[0047] Preparation of positive electrode
[0048] The following materials were put into an MP mixer (Nippon Coke Industry Co., Ltd.), and composite treatment was performed at 10,000 rpm for 10 minutes to fix the conductive material on the surface of the active material particles with a binder.
[0049] Positive electrode active material particles: NCM (volume average particle size: 10 μm, 96.6 parts by mass)
[0050] Conductive material: acetylene black (1.5 parts by mass)
[0051] Adhesive: PVdF (0.5 parts by mass)
[0052] PTFE (1.4 parts by mass) was further added to the MP mixer after the composite treatment, and mixed at 300 rpm for 180 seconds, and then further mixed at 5000 rpm for 500 seconds to form granules in which the active material particles were bound by the fibrillated PTFE.
[0053] The mixture including the granules was rolled using a roll press (linear pressure: 0.4 t / cm) to fiberize the PTFE and form it into a sheet (thickness: 120 μm).
[0054] The sheet-shaped molded body and an aluminum foil (thickness: 12 μm) as a current collector were bonded together using a roll press (linear pressure: 4 t / cm, 160° C.).
[0055] Comparative Example
[0056] Preparation of positive electrode
[0057] The following materials were put into an MP mixer (Japan Coke Industry Co., Ltd.) and mixed at 300 rpm for 180 seconds. Then, they were further mixed at 5000 rpm for 500 seconds to form a granulated body in which the active material particles were bonded with fibrous PTFE. The amount of the binder was set to a total volume equal to the total volume of the binder used in Example 1.
[0058] Positive electrode active material particles: NCM (volume average particle size: 10 μm, 96.5 parts by mass)
[0059] Conductive material: acetylene black (1.5 parts by mass)
[0060] Binder: PTFE (2.0 parts by mass)
[0061] The mixture containing the granules was rolled using a roll press (linear pressure: 0.4 t / cm) to fibrousize the PTFE and form a sheet (thickness: 10 μm). The sheet was laminated to an aluminum foil (thickness: 12 μm) as a current collector using a roll press (linear pressure: 4 t / cm, 160°C).
[0062] Evaluation of coverage rate
[0063] The positive electrodes prepared in the examples and comparative examples were cut, the obtained cross sections were observed with a SEM, C mapping was performed using EDX attached to the SEM, and the coverage of the active material particles with the conductive material was calculated.
[0064] Evaluation of electronic conductivity
[0065] As an index of the electron conductivity of the positive electrodes prepared in the examples and comparative examples, the resistance inside the electrode layer (electrode layer resistance) and the resistance at the interface between the electrode layer and the current collector (interface resistance) were measured using an electrode resistance measurement system RM2610 (Hioki Electric Co., Ltd.). The results are shown in Table 1.
[0066] A small battery cell for measuring IV resistance was prepared using the positive electrode prepared in the examples and comparative examples and the negative electrode prepared by the following method. The IV resistance was calculated by the following method using the small battery cell. The results are shown in Table 1.
[0067] Measurement method: Discharge with a current of 0.3C for 10 seconds and measure the voltage drop ΔV during 10 seconds. Calculate the IV resistance from the relationship between the current I and ΔV.
[0068] Negative electrode preparation
[0069] A negative electrode was prepared by applying a paste containing graphite (volume average particle size: 20 μm, 98 parts by mass) as a negative electrode active material, carboxymethyl cellulose (0.4 parts by mass) and SBR (1.6 parts by mass) as a binder on a copper foil (thickness: 8 μm) as a current collector.
[0070] (Table 1)
[0071]
[0072] As shown in Table 1, the positive electrode of the embodiment made of active material particles and PTFE with conductive material fixed on the surface by an adhesive has a larger coverage rate of the conductive material of the active material than the positive electrode of the comparative example made of active material particles and PTFE without using an adhesive to fix the conductive material on the surface. Furthermore, the positive electrode of the embodiment made of active material particles and PTFE with conductive material fixed on the surface by an adhesive has a lower electrode layer resistance, interface resistance and IV resistance than the positive electrode of the comparative example made of active material particles and PTFE without using an adhesive to fix the conductive material on the surface. The above results suggest that fixing the conductive material on the surface of the active material particles with an adhesive can increase the coverage rate of the conductive material of the active material particles, thereby contributing to the improvement of electronic conductivity.
Claims
1. A method for manufacturing an electrode, comprising: a step of kneading the active material particles, the conductive material, and the binder to fix the conductive material to at least a portion of the surface of the active material particles; A step of mixing active material particles to which a conductive material is fixed by a binder with polytetrafluoroethylene to obtain a mixture; and A step of fiberizing the polytetrafluoroethylene in the mixture.
2. The method for manufacturing an electrode according to claim 1, wherein: The coverage of the active material particles by the conductive material is 10% or more.
3. An electrode comprising a current collector and an electrode layer, wherein the electrode layer comprises active material particles having a conductive material fixed to at least a portion of the surface thereof by a binder, and fibrous polytetrafluoroethylene.
4. The electrode according to claim 3, wherein The coverage of the active material particles by the conductive material is 10% or more.
5. A battery comprising the electrode according to claim 3 or 4.
Citation Information
Patent Citations
Electrode film for energy storage device, electrode and energy storage device
JP2022003694A